Junior secondary students' acceptance and continuance of e-learning system use: a multi-group analysis across social backgrounds. Issue 2 (25th January 2022) - Cheng, Miaoting; Yuen, Allan H. K.
ABSTRACT: Although previous research into adults' acceptance or continued use of technology has been extensive, there is a lack of research study that investigated e-learning systems acceptance and continuance of teenagers with different social backgrounds. This study aimed to explore the cognitive, emotional, and behavioural factors that motivate teenagers' acceptance and continuance of e-learning system use, and to compare such system use behaviours across teenagers with different social backgrounds. Drawing on the theory of reasoned action, the technology acceptance model, and the expectation-confirmation model, a research model was proposed and tested using data from a three-wave longitudinal survey on 1182 junior secondary students. Structural equation modelling (SEM) was used to test the model with the entire sample. The results showed that perceived ease of use, peer subjective norm, and teacher subjective norm were strong motivators of behavioural intention at all use stages. Multi-group SEM analysis was conducted across teenagers with different gender, experience, and socio-economic status. The results showed significant path differences in all group comparisons, revealing the existence of social divides in the modelled relationships. The majority of these path differences were found in the relationships between satisfaction and its antecedent variables. The findings and implications are discussed.